Risk of subsequent colorectal cancers after a solid tumor in childhood: Effects of radiation therapy and chemotherapy. Issue 2 (21st October 2018) - Allodji, Rodrigue S.; Haddy, Nadia; Vu‐Bezin, Giao; Dumas, Agnès; Fresneau, Brice; Mansouri, Imene; Demoor‐Goldschmidt, Charlotte; El‐Fayech, Chiraz; Pacquement, Hélène; Munzer, Martine; Bondiau, Pierre‐Yves; Berchery, Delphine; et al.
Abstract: Background: Very few previous studies have addressed the question of colorectal cancer (CRC) after childhood cancer treatment. We aimed to quantify the roles of radiation therapy and chemotherapy agents in the occurrence of subsequent CRC. Methods: A nested case–control study was conducted using 36 CRC cases and 140 controls selected from 7032 five‐year survivors of the French Childhood Cancer Survivor Study (FCCSS) cohort, treated from 1945 to 2000 in France. The radiation dose‐distribution metrics at the site of CRC and doses of individual chemotherapeutic agents were calculated. Conditional logistic regressions were performed to calculate odds ratios (ORs). Results: Overall, patients who received radiotherapy with estimated dose to colon had a 4.3‐fold (95% CI, 1.3–17.6) increased risk for CRC compared with patients who did not receive radiotherapy, after adjustment for chemotherapy. This risk increased to 8.9‐fold and 19.3‐fold among patients who received radiation doses ranging from 20 to 29.99 Gy and ≥30 Gy, respectively. Our data reported a significantly elevated OR for anthracyclines, after controlling for radiotherapy and MOPP regimen. But, restricted analyses excluding patients who had received ≥30 Gy showed that only radiation doses ranging from 20 to 29.99 Gy produced a significant increase in subsequent CRC risk (OR = 7.8; 95% CI, 1.3–56.0), after controlling for anthracyclines and MOPP regimen. Conclusions: The risk of subsequent CRC was significantly increased after radiation dose (even < 30 Gy). This novel finding supports the need to update monitoring guidelines for CRC to optimize the long‐term follow‐up for subsequent CRC in survivors of childhood cancer.